2014
DOI: 10.1002/mabi.201400071
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-Hydroxyethyl Methacrylate)-b-Poly(L-Lysine) Cationic Hybrid Materials for Non-Viral Gene Delivery in NIH 3T3 Mouse Embryonic Fibroblasts

Abstract: In order to develop efficient and nontoxic gene delivery vectors, a series of biocompatible block copolymers, poly[(2-hydroxyethyl methacrylate)40 -block-(L-lysine)n ] (n = 40, 80, 120, 150), are prepared by combining an atom transfer radical polymerization of 2-hydroxyethyl methacrylate with a ring-opening polymerization of N(ϵ) -(carbobenzoxy)-L-lysine N-carboxyanhydride. The block copolymers are successfully condensed with plasmid DNA (pDNA) into nanosized (<200 nm) polyplexes. As a representative sample, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Principally, in the presence of aqueous ions and other charged species, polyplexes tend to aggregate with themselves or other biomolecules such as serum proteins, which severely limits the targeting potential of polyplexes to specific tissues when delivered through the circulatory systems of whole animals. ,, For example, polyplexes formed with PEI become trapped in the lungs during first-pass circulation due to aggregation upon systemic injection. , Moreover, PEI polyplexes also suffer from rapid clearance from the blood by the reticuloendothelial system due to nonspecific charge-mediated interactions with serum proteins. , To prevent these detrimental interactions, polyethylene glycol (PEG) is commonly used as a hydrophilic outer layer to sterically stabilize polyplexes from aggregation and prolong circulation times by reducing nonspecific interactions with the reticuloendothelial system. , However, PEG has a limited effect on polyplex stability and undergoes accelerated blood clearance after multiple injections. , Several other structures have been explored as alternatives to PEG to achieve colloidal stability and biocompatibility. These include zwitterionic structures like polysulfobetaine, biodegradable polymers such as poly­(2-hydroxyethyl methacrylate) and poly­(lactic- co -glycolic acid). Earlier work from our lab has demonstrated that diblock polymers containing glucose or trehalose-substituted monomers copolymerized with a cationic block form colloidally stable polyplexes and offer potential as alternative hydrophilic coating layers. , These sugar-derived neutral blocks form a “stealth” layer that prevents aggregation while maintaining excellent gene-delivery properties in cultured cells. , …”
Section: Introductionmentioning
confidence: 99%
“…Principally, in the presence of aqueous ions and other charged species, polyplexes tend to aggregate with themselves or other biomolecules such as serum proteins, which severely limits the targeting potential of polyplexes to specific tissues when delivered through the circulatory systems of whole animals. ,, For example, polyplexes formed with PEI become trapped in the lungs during first-pass circulation due to aggregation upon systemic injection. , Moreover, PEI polyplexes also suffer from rapid clearance from the blood by the reticuloendothelial system due to nonspecific charge-mediated interactions with serum proteins. , To prevent these detrimental interactions, polyethylene glycol (PEG) is commonly used as a hydrophilic outer layer to sterically stabilize polyplexes from aggregation and prolong circulation times by reducing nonspecific interactions with the reticuloendothelial system. , However, PEG has a limited effect on polyplex stability and undergoes accelerated blood clearance after multiple injections. , Several other structures have been explored as alternatives to PEG to achieve colloidal stability and biocompatibility. These include zwitterionic structures like polysulfobetaine, biodegradable polymers such as poly­(2-hydroxyethyl methacrylate) and poly­(lactic- co -glycolic acid). Earlier work from our lab has demonstrated that diblock polymers containing glucose or trehalose-substituted monomers copolymerized with a cationic block form colloidally stable polyplexes and offer potential as alternative hydrophilic coating layers. , These sugar-derived neutral blocks form a “stealth” layer that prevents aggregation while maintaining excellent gene-delivery properties in cultured cells. , …”
Section: Introductionmentioning
confidence: 99%
“…12,13 To date, cationic polymers such as poly(ethylenimine), polyamidoamine dendrimer, poly(Llysine), and their derivatives have been successfully applied in p53 gene delivery. [14][15][16][17][18][19][20][21] Apart from these cationic polymers, copolyester poly(amine-co-ester)s containing tertiary amino substituents have also been widely employed as gene vectors owing to their unique features such as high transfection efficiency, favorable biocompatibility and biodegradability, and ease of production. 22,23 Generally, poly(amine-co-ester)s are synthesized in a chemical manner, in which the trace residue and underlying toxicity of metallic catalysts may limit the clinical applications of products.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the incorporation of hydrophilic polymers as poly[ N ‐(2‐hydroxypropyl) methacrylamide] (PHPMA), poly[(2‐hydroxyethyl methacrylate)] (PHEMA), poly( N ‐isopropylacrylamide) (PNIPAM) into the PLL. However, one of the most extensively used hydrophilic synthetic segment in the hybrid copolymers is poly(ethylene glycol) (PEG) .…”
Section: Introductionmentioning
confidence: 99%